The Nature of the Adsorption of Nucleobases on the Gold [111] Surface - Piana, Stefano; Bilic, Ante (American Chemical Society, 2006)
Biochip technology is based on the immobilization of biological macromolecules on the surface of electronic devices. The biochemical properties of the immobilized molecules can be influenced to a large extent by the interaction with the inorganic surface. The interaction of DNA with the surface of gold, a metal commonly used in biochip technologies, is sequence dependent as the four nucleobases, adenine, thymine, cytosine, and guanine, interact to a different extent with the gold surface. The nature of nucleobase adsorption on the gold [111] surface has been investigated by performing density functional theory and post-Hartree-Fock calculations. It turns out that the interaction is dominated by dispersion forces and an appreciable degree of chemisorption is observed for adenine only. A set of Lennard-Jones parameters that describe the interaction was derived from the post-Hartree-Fock calculations. Classical molecular dynamics simulations of nucleobase monolayers based on these parameters are in remarkable agreement with the experiment and show that the interaction of the nucleobases with the gold surface is strongly modulated by base-base interations and reaches a maximum when a full monolayer is formed.